2016
DOI: 10.1038/srep33325
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged California aridity linked to climate warming and Pacific sea surface temperature

Abstract: California has experienced a dry 21st century capped by severe drought from 2012 through 2015 prompting questions about hydroclimatic sensitivity to anthropogenic climate change and implications for the future. We address these questions using a Holocene lake sediment record of hydrologic change from the Sierra Nevada Mountains coupled with marine sediment records from the Pacific. These data provide evidence of a persistent relationship between past climate warming, Pacific sea surface temperature (SST) shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Thus, we further suggest these differential trends in dryness for NorCal and SoCal may be caused by the PDO/ENSO-related seesaw of hydroclimatic variability over the Pacific Northwest and Southwest. The climatic drying might be partly attributed to the anthropogenic warming-induced increase of atmospheric evaporative demand (MacDonald et al, 2016;Naumann et al, 2018;Williams et al, 2015). It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal).…”
Section: Drought and Climate Change In Californiasupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, we further suggest these differential trends in dryness for NorCal and SoCal may be caused by the PDO/ENSO-related seesaw of hydroclimatic variability over the Pacific Northwest and Southwest. The climatic drying might be partly attributed to the anthropogenic warming-induced increase of atmospheric evaporative demand (MacDonald et al, 2016;Naumann et al, 2018;Williams et al, 2015). It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal).…”
Section: Drought and Climate Change In Californiasupporting
confidence: 82%
“…It is consistent with Deitch et al (2017) who reported significantly reduced (increased) precipitation during the past half-century in SoCal (NorCal). The climatic drying might be partly attributed to the anthropogenic warming-induced increase of atmospheric evaporative demand (MacDonald et al, 2016;Naumann et al, 2018;Williams et al, 2015). In projections of precipitation change in the Coupled Model Intercomparison Project Phases 3 and 5, precipitation reductions are predicted for the subtropics and increases for middle to high latitudes along the Pacific coast of North America (Chang et al, 2015;Neelin et al, 2013;Seager et al, 2013;Wang & Kotamarthi, 2015).…”
Section: Drought and Climate Change In Californiamentioning
confidence: 99%
“…Precipitation has begun to exhibit either a long-term downward trend, mainly in the dry season [22], or no significant change [2,3,20] although in all cases a rise in potential evapotranspiration has led to increased aridity [2,3]. In South California and South Africa similar trends have been observed in the recent past and are projected for the coming decades [23,24].…”
Section: Current Climate Changementioning
confidence: 84%
“…ery is an open question, given the expectation of ever more variable and extreme conditions (Cook et al, 2015;MacDonald et al, 2016;Wang et al, 2017), and given that most plants are unlikely to disperse fast enough to keep up with rapid climatic shifts (Corlett & Westcott, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Droughts are likely to become more frequent and severe in the coming century, not only because altered oceanic and atmospheric circulation will diminish the supply of rainfall in many regions, including those with Mediterranean‐type climates, but also because rising temperatures will drive substantial increases in evaporative demand (Collins et al., ; Cook, Ault, & Smerdon, ; MacDonald et al., ). Ecologically, the impacts of drought are likely to be intensified by the joint effects of higher temperatures and less rainfall on ecosystem processes (e.g.…”
Section: Introductionmentioning
confidence: 99%